Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jval.2015.09.2133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Diabetes Patients’ Preferences for Profiles of Glp-1 Treatments In The United Kingdom: A Discrete Choice Experiment

Abstract: This analysis suggests that IDegLira provides a statistically significant improvement in health utility compared with IGlar, in patients with T2D inadequately controlled on IGlar and metformin. The health utility improvement was generally driven by improvement in physical health, while mental health remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Weekly injections have the potential to improve patient perceptions. In fact, a study of injection-naive patients with T2D demonstrated that 83% of patients' significantly preferred a once weekly dulaglutide medication profile compared to a once daily liraglutide medication profile (p ≤ 0.0001) [35].…”
Section: Device and Delivery Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weekly injections have the potential to improve patient perceptions. In fact, a study of injection-naive patients with T2D demonstrated that 83% of patients' significantly preferred a once weekly dulaglutide medication profile compared to a once daily liraglutide medication profile (p ≤ 0.0001) [35].…”
Section: Device and Delivery Benefitsmentioning
confidence: 99%
“…Two such studies involved obtaining stated preferences from patients with T2D. In the first study, using discrete choice experiment (DCE) methodology, in-person interviews were conducted in the UK with injection-naive patients with T2D [35]. The DCE examined six attributes of T2D treatment associated with dulaglutide and liraglutide: 'dosing frequency,' 'HbA1c change,' 'weight change,' 'type of delivery system,' 'frequency of nausea,' and 'frequency of hypoglycemia.'…”
Section: Pros In Dulaglutide Clinical Trialsmentioning
confidence: 99%